Hubungan asupan lemak, karbohidrat, zat besi (Fe) dan Kurang Energi Kronik (KEK) dengan kejadian anemia pada remaja putri di SMAN 1 Parigi Kabupaten Muna - Rahim, Marlin; Sabilu, Yusuf; Yunawati, Irma (Indonesian Journal of Health Science, 2024)
Anemia is a nutritional problem that often occurs in developing countries, one of which is Indonesia, which is most often experienced by young women. The aim of this study was to determine the relationship between fat intake, carbohydrate intake and KEK with the incidence of anemia in adolescent girls at SMAN 1 Parigi. The type of research used is quantitative with a cross sectional approach. The population in this study were all young women at SMAN 1 Parigi in grades X and XI, totaling 113 female students. The sample size was determined based on the Slovin formula so that a sample of 88 female students was obtained. The sampling technique used was proportionate random sampling with inclusion and exclusion criteria. Data analysis used the chi square test. The results of the study showed that there was no relationship between fat and carbohydrates and the incidence of anemia with a p value = 0.109; 0.296 (p>0.05), and there is a relationship between the mineral Fe and KEK and the incidence of anemia in female students at SMAN 1 Parigi with a value of p=0.000; 0.000 (p<0.05). It is hoped that female students can pay attention to the intake they consume, especially foods high in fat, carbohydrates, Fe minerals, and also maintain their diet so as to avoid anemia and CED. Anemia merupakan masalah gizi yang banyak terjadi di Negara-negara berkembang  salah satunya Indonesia yang paling banyak dialami oleh remaja putri. Tujuan penelitian ini untuk mengetahui hubungan asupan lemak, asupan karohidrat dan KEK dengan kejadian anemia pada remaja putri di SMAN 1 Parigi Kabupaten Muna. Jenis penelitian yang digunakan adalah kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini yaitu seluruh remaja putri SMAN 1 Parigi dengan jenjang kelas X dan XI yang berjumlah 113 siswi. Besar sampel ditetapkan berdasarkan rumus Slovin sehingga diperoleh sampel sebanyak 88 siswi. Teknik pengambilan sampel yang digunakan adalah proportionate random sampling dengan kriteria inklusi dan eksklusi. Analisis data menggunakan uji chi square. Hasil penelitian menunjukan tidak terdapat hubungan antara lemak serta karbohidrat dengan kejadian anemia dengan nilai p=0,109; 0,296 (p>0,05), serta terdapat hubungan antara mineral Fe dan KEK dengan kejadian anemia pada siswi di SMAN 1 Parigi dengan nilai p=0,000; 0,000 (p<0,05). Diharapkan agar siswi dapat memperhatikan asupan yang mereka konsumsi terutama makanan tinggi zat lemak, karbohidrat, mineral Fe, dan  serta menjaga pola makan sehingga terhindar dari anemia dan KEK.